High precise and zero-cost solution for fully automatic industrial robot TCP calibration. Issue 5 (17th July 2019) - Cakir, Mustafa; Deniz, Cengiz
Abstract : Purpose: The purpose of this study is to present a novel method for industrial robot TCP (tool center point) calibration. The proposed method offers fully automated robot TCP calibration within a defined cycle time. The method is applicable for large-scale installations due to its zero cost for each robot. Design/methodology/approach: Precise and expensive measuring equipment or specially designed reference devices are required for robot calibration. The calibration can be performed by using only one plane plate in this method, and the calibration procedure is defined step by step: the robot moves to the target plane position. Then, the TCP touches the plane and the actual robot configuration is recorded. Then robot moves back into position and the same step is repeated for a new sample. Alternatively, the robot can be stationary and the plane can be moved towards the robot TCP. TCP is calculated by processing the difference of the contact points recorded at different positions. The process is fully automated. No special equipment is used. The calculations are very simple, and the robot controller can easily be realized. Findings: The conventional manual robot TCP calibration process takes about 15 min and takes more time in case of the high accuracy. The proposed method reduces this time to less than 3 min without operator support. Practical tests have shown that TCP calibration can be performed with 0.1-0.6 mm of accuracy. This solution is an automated process and does not require special installation and it also has approximately zero cost. For this reason, this study recommends using the proposed solution widely in areas where even one or hundreds of robots are located. Research limitations/implications: In this study, the data were directly taken from the robot controller without using any special measuring equipment. The industrial robot used in the tests has no absolute calibration. The classical "four-point method" was used for reference TCP data. It is the initial acceptance that this process conducted with extreme care and by using a needle-tipped tool will not produce exact values. It was observed that deviation of the TCP from a fixed point in reorient motions was not more than 0.5 mm. This method has been validated for different bits. The pilot works for different robot applications in Ford Otosan Gölcük Plant have been completed and dissemination has started. Originality/value: Although the approach uses is clear and simple, it is surprising that the calculation of TCP using plane equations has so far not been mentioned in the literature. The disadvantage of using either fixed point or sphere as a reference is that the TCP cannot automatically guide to the target. This problem was overcome with the use of a larger target plane plate and the process was fully automated. The proposed method can be widely used in practical applications.